Psychology and pediatric dentistry: the contribution of behaviour functional analysis / Psicologia e odontopediatria: a contribuição da análise funcional do comportamento - Antonio Bento Alves de Moraes; Kira Anayansi Singh Sanchez; Rosana de Fátima Possobon; Áderson Luiz Costa Júnior (Psicologia: Reflexão e Crítica, 2004)
The aim of this study was to carry out a functional description of the pediatric dentists' behavior concerning professional performance. Subjects were 3 uncooperative dental patients who were treated using placebo or diazepam. Dental sessions were videotaped. Procedures and behaviors were recorded in 15-second intervals. Results revealed that children's level of cooperative behavior may be a considered variable that affect professional behaviors. Diazepam was not effective. "Guidance" was predominantly used by the dentist and evoked cooperative behavior with two patients. The results express the contribution of behaviour functional analysis to the study of patterns of interaction between the dental practitioner and child patient.